2018
DOI: 10.1002/hrm.21915
|View full text |Cite
|
Sign up to set email alerts
|

Building knowledge stock and facilitating knowledge flow through human resource management practices toward firm innovation

Abstract: The present study theoretically identifies the meaningful human resource management (HRM) practices that explain the emergence of two distinct dimensions of firm-level knowledge management, namely, firm knowledge stock and flow, which are critical drivers of firm innovation.We also propose that these knowledge dimensions interact synergistically and that their effects on firm innovation are accentuated in firms with strong innovation strategy. The proposed theoretical framework was tested using multisource,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 68 publications
1
27
0
2
Order By: Relevance
“…This study offers several practical insights into the improvement of knowledge sharing in organizations, which is critical for team and organizational performance and innovation (Sung & Choi, , in press). Given the considerable effects of the two facets of conscientiousness on knowledge‐sharing behavior, recruiting highly conscientious employees is a reasonable strategy for enhancing interpersonal and task performance outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study offers several practical insights into the improvement of knowledge sharing in organizations, which is critical for team and organizational performance and innovation (Sung & Choi, , in press). Given the considerable effects of the two facets of conscientiousness on knowledge‐sharing behavior, recruiting highly conscientious employees is a reasonable strategy for enhancing interpersonal and task performance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…An organization's capability to effectively leverage its knowledge depends on its employees because individuals are the primary holders and movers of knowledge (Nonaka, ). Previous studies have contended that the benefit of the stock or amount of knowledge is limited unless such knowledge is shared across the members of a group or organization (Sung & Choi, , in press). Knowledge sharing represents a paradigmatic social exchange situation known as a “social dilemma” because this action can benefit the collective but may undermine the position and advantage of knowledge contributors (Cabrera & Cabrera, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that sixty per cent of employees found it difficult to obtain information from colleagues (Inefficient Knowledge Sharing Costs Large Businesses $47 Million Per Year https://www.prnewswire.com/news-releases/inefficient-knowledge-sharing-costs-large-businesses-47-million-peryear-300681971.html). Nevertheless, it has been confirmed that the effectiveness of an explicit knowledge application depends on its fluent transfer between employees (Sung, Choi 2018;Chae et al 2019). Hence, it is important that managers facilitate explicit knowledge transfer in organizations.…”
Section: Workplace Collaboration and Explicit Knowledge Transfermentioning
confidence: 98%
“…Den teknologiske udvikling har haft markant indvirkning på de tematikker, som berøres i nyere HRforskning (Stone og Deadricks, 2015;Björkman & Welch, 2015;Marler & Boudreau, 2016;Sung & Choi, 2018 (Junni et al 2015).…”
Section: Teknologisk Udviklingunclassified
“…Den øgede diversitet er således afgørende at forholde sig aktivt til for at kunne profitere frem for udfordres af den.9. Kommunikation og vidensdelingKommunikation, samarbejde og vidensdeling er afgørende parametre for, at organisationer kan skabe vaerdi(Sung & Choi 2018). Derfor har HR-afdelinger et ansvar for at samarbejde taet med ledere og sikre arbejdsfordeling på en sådan vis, at det gøres attraktivt at samarbejde og dele viden Det er jo dialogen omkring det, der er vigtig.…”
unclassified